2000
DOI: 10.1046/j.1432-1327.2000.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized galectin-1 promotes axonal regeneration in peripheral nerves but does not possess lectin properties

Abstract: Galectin-1 has recently been identified as a factor that regulates initial axonal growth in peripheral nerves after axotomy. Although galectin-1 is a well-known b-galactoside-binding lectin, its potential to promote axonal regeneration as a lectin has not been reported. It is essential that the process of initial repair in peripheral nerves after axotomy is well clarified. We therefore undertook to investigate the relation between the structure and axonal regeneration-promoting activity of galectin-1. Recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 17 publications
6
41
0
1
Order By: Relevance
“…amounts of both PP13-B and PP13-R induced haemagglutination, and strong agglutination was detected at and above 50 lgAEmL )1 applied protein concentrations ( Fig. 4), which was very similar to the phenomenon seen in cases of other galectins [35]. The pattern and effectiveness of both PP13-B and PP13-R were identical in agglutination of erythrocytes.…”
Section: Pp13/galectin-13 Possesses Lectin Activitysupporting
confidence: 74%
“…amounts of both PP13-B and PP13-R induced haemagglutination, and strong agglutination was detected at and above 50 lgAEmL )1 applied protein concentrations ( Fig. 4), which was very similar to the phenomenon seen in cases of other galectins [35]. The pattern and effectiveness of both PP13-B and PP13-R were identical in agglutination of erythrocytes.…”
Section: Pp13/galectin-13 Possesses Lectin Activitysupporting
confidence: 74%
“…In axotomy experiments, galectin-1 was shown to promote axonal regeneration and Schwann cell migration (Horie et al, 1999). The protective effects of galectin-1 were suggested to be caused by an oxidized monomeric form, unable to bind to galactose (Inagaki et al, 2000). In contrast, our protein contained both monomeric and dimeric fractions.…”
Section: Discussionmentioning
confidence: 84%
“…However, in 1991 Hirbayashi and Kasai substituted serine for cysteine residues and demonstrated that these mutants exhibited virtually no change in the ability of galectin-1 (Gal-1) to bind to asialofetuin-agarose [20]. These results were corroborated by subsequent studies and demonstrated that the cysteine residues of Gal-1 are not necessary for glycanbinding [20][21][22][23]. Instead, these studies demonstrated that the reduced thiols of cysteine residues are important for maintaining protein stability and that oxidation at such residues eliminates Gal-1 carbohydrate binding activity [20][21][22][23].…”
Section: Key Regulators Of Galectin Activitymentioning
confidence: 98%
“…While the unique sensitivity of Gal-1 to oxidative inactivation can complicate the study of Gal-1 in biological systems [29,40], the ability of redox potential to regulate carbohydrate independent activities of Gal-1 represents a relatively unexplored, yet critical factor responsible for Gal-1 function [23,27,36,41,42]. This is especially important when considering that while oxidation appears to impact the carbohydrate binding capacity of Gal-1, subsequent studies suggested that oxidized Gal-1 actually possesses biological activity that occurs through glycan-independent processes [23,36,41,[43][44][45][46]. Indeed, oxidized Gal-1 appears to regulate neurite outgrowth and may be important in overall neuron regeneration following injury [23,36,41,[43][44][45][46][47].…”
Section: Key Regulators Of Galectin Activitymentioning
confidence: 99%
See 1 more Smart Citation